2001
DOI: 10.1038/sj.onc.1204315
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ha-ras activation in superficial papillary pathway of urothelial tumor formation

Abstract: Urothelial tumors develop along two distinctive phenotypic pathways (super®cial papillary non-invasive tumors versus¯at carcinoma in situ lesions), with markedly di erent biological behavior and prognosis. Although multiple genetic alterations have been identi®ed in human bladder cancer, their cause ± e ect relationship with the two pathways has not been ®rmly established. Using a urothelium-speci®c promoter of the uroplakin II gene, we showed earlier in transgenic mice that the urothelial expression of SV40T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
117
2
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(128 citation statements)
references
References 44 publications
4
117
2
1
Order By: Relevance
“…Finally, we found a significant association of the impaired DNp63 expression with reduced b-catenin expression that relates to a worse prognosis of bladder cancer patients (Garcia del Muro et al, 2000;Shimazui et al, 1996). Recently, experimental studies on transgenic mice have provided strong evidences that different genetic defects are responsible for the two distinctive pathways of urothelial tumorigenesis (Zhang et al, 1999(Zhang et al, , 2001). Activation of Ha-ras alone, which plays a central role in mitogenic signal transduction, induces urothelial hyperplasia and papillary noninvasive tumours but not invasive carcinomas (Zhang et al, 2001), indicating that increased cell proliferation alone can lead to development of the papillary noninvasive urothelial tumour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we found a significant association of the impaired DNp63 expression with reduced b-catenin expression that relates to a worse prognosis of bladder cancer patients (Garcia del Muro et al, 2000;Shimazui et al, 1996). Recently, experimental studies on transgenic mice have provided strong evidences that different genetic defects are responsible for the two distinctive pathways of urothelial tumorigenesis (Zhang et al, 1999(Zhang et al, , 2001). Activation of Ha-ras alone, which plays a central role in mitogenic signal transduction, induces urothelial hyperplasia and papillary noninvasive tumours but not invasive carcinomas (Zhang et al, 2001), indicating that increased cell proliferation alone can lead to development of the papillary noninvasive urothelial tumour.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, experimental studies on transgenic mice have provided strong evidences that different genetic defects are responsible for the two distinctive pathways of urothelial tumorigenesis (Zhang et al, 1999(Zhang et al, , 2001). Activation of Ha-ras alone, which plays a central role in mitogenic signal transduction, induces urothelial hyperplasia and papillary noninvasive tumours but not invasive carcinomas (Zhang et al, 2001), indicating that increased cell proliferation alone can lead to development of the papillary noninvasive urothelial tumour. On the other hand, inactivation of p53 and pRb by SV40 large T antigen induces CIS, invasive carcinoma, and metastatic disease (Zhang et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…This promoter exhibits several properties that are important for transgenesis: (1) it functions in a strictly urothelium-specific manner; (2) it is active in all mouse urothelial layers, including the basal layer that is more susceptible to oncogenic transformation; and (3) its expression persists even after malignant transformation (Lin et al, 1995;Zhang et al, 1999). Using this promoter to develop transgenic mouse models, we found that urothelial expression of an activated Ha-ras can induce urothelial hyperplasia and low-grade, superficial papillary tumors (Zhang et al, 2001).…”
mentioning
confidence: 99%
“…This promoter exhibits several properties that are important for transgenesis: (1) it functions in a strictly urothelium-specific manner; (2) it is active in all mouse urothelial layers, including the basal layer that is more susceptible to oncogenic transformation; and (3) its expression persists even after malignant transformation (Lin et al, 1995;Zhang et al, 1999). Using this promoter to develop transgenic mouse models, we found that urothelial expression of an activated Ha-ras can induce urothelial hyperplasia and low-grade, superficial papillary tumors (Zhang et al, 2001). The onset of the bladder tumors depends on the dosage of the uroplakin II-Ha-ras transgene, as mice harboring 30-50 copies of the transgene develop tumors at 4-5 months of age and mice harboring 1-2 copies of the transgene develop only urothelial hyperplasia before 10 months of age, after which 63% of the mice develop the bladder tumors (Zhang et al, 2001).…”
mentioning
confidence: 99%
“…These "superficial" tumors are therefore rarely lethal, but their high recurrence rates coupled with patient longevity make them the most expensive solid tumors to treat and therefore a significant public health burden. Superficial tumors are thought to be driven by Ras pathway activation (2), most often (in up to 65% of cases) via the accumulation of activating mutations in the type 3 fibroblast growth factor receptor (3) and less often via mutations in phosphoinositide 3-kinase (4) or Ras itself. The second progression track involves the inactivation of major tumor suppressors [p53, Rb, and phosphatase and tensin homologue (PTEN); refs.…”
mentioning
confidence: 99%